TERTIARY EDUCATION IN NIGERIA AND CONFLICT MANAGEMENT STRATEGIES - Umoru , Abdulrasheed Oseni (Multi-Disciplinary Research and Development Journals Int’l, 2025)
Conflict is an inevitable feature of tertiary institutions where diverse groups interact under sometimes-stressful conditions. In Nigeria, conflicts in universities and other tertiary institutions arise from funding shortfalls, infrastructure deficits, poor communication, union–management disputes, cultism, ethnic and political tensions, and cases of sexual harassment. This chapter clarifies the concepts of conflict and conflict management, identifies the major causes of campus conflict, and outlines practical management strategies — including dialogue and negotiation, mediation, arbitration, grievance mechanisms, conflict-resolution committees, skills training, and the promotion of a culture of peace and inclusion. The chapter argues that proactive, transparent, and participatory approaches to conflict management can transform destructive conflicts into opportunities for institutional learning and sustainable campus governance.